Electronic and optical properties of group V one-dimensional materials with a square columnar structure: A first-principles investigation - Pinbo Huang; Zhiang Liu; Ping Huang; Yi Luo (Results in Physics)
In this paper, we propose a series of novel one-dimensional group V semiconductors with a square columnar structure, denoted as SC-As, SC-Sb, and SC-Bi, derived from SC-P. Phonon dispersion calculations reveal their dynamic stability, while first-principles calculations show versatilities in their electronic and optical properties influenced by spin–orbit coupling. SC-P, SC-As, and SC-Sb exhibit strong sunlight absorption with intensities exceeding 3 × 105 cm−1, while SC-Bi demonstrates exceptional absorption spanning the entire solar flux spectrum. Furthermore, band alignment denotes that the SC-P is suitable for photocatalytic water splitting in both acidic and alkaline environments, while SC-As and SC-Sb work in alkaline conditions. These findings unveil the potential of these materials in solar energy harvesting and photocatalytic hydrogen production, advancing the development of group V 1D semiconductors.